Performance of a twin-intake diesel engine with a bionic functional surface during an intake process - Yunzhen Guo; Hailin Kui; Wenyu Liu; Jun Chen (Case Studies in Thermal Engineering)
Intake swirl is an important factor affecting the combustion characteristics of a semi-open combustion chamber diesel engine, which provides energy for the formation of the mixture. To provide a twin-intake diesel engine with a strong intake swirl, this study uses the surface morphology of shark skin and insects as bionic template extracts and optimizes the element morphology and size. The designed bionic microstructures of grooves and pits are used to construct a synergistic functional surface for twin-intake diesel engines. A comprehensive test with 2 levels and 3 factors is conducted to determine 9 groups of different twin-intake combination schemes. The flow characteristics are verified via steady-flow bench tests. The intake process of twins with different bionic functional surfaces is analyzed via computational fluid dynamics (CFD). Taking a visualized optical engine as the test platform, the turbulent motion in the cylinder of a diesel engine with different twin-intake combined bionic functional surfaces is studied with the help of particle image velocity (PIV). The results show that different combined bionic microfunctional surface structures have little effect on the flow coefficient of diesel engines but have an obvious enhancement effect on the swirl ratio. When the tangential port is a groove-type bionic microstructure and the helical port is a pit-type bionic microstructure, the increase in the flow coefficient is 0.94 %, and the increase in the swirl ratio is 13.75 % at the maximum valve lift. There are many large-scale vortex core regions in the cylinder. The enhancement effect of the swirl ratio is the most obvious. Improving the intake swirl is highly important for improving the combustion efficiency and reducing the fuel consumption of diesel engines.